DETERMINATION OF THE INNOVATIVE TRAJECTORY OF A MODERN EDUCATIONAL INSTITUTION DEVELOPMENT: VALUABLE AND SENSE ORIENTATIONS - Olena Lavrinenko (Borys Grinchenko Kyiv Metropolitan University, 2022)
The article considers innovative activity and research and experimental work as the main factors in the innovative development of a modern educational institution. The need to understand the research and experimental work as an essential component of innovation, as a conscious effective tool for understanding the reform of the traditional school system in innovation is explained. The article examines the value and semantic orientations of teachers, and heads of educational institutions as certain guidelines in the situation of choosing the direction of innovative search by the teaching staff, determining the innovative trajectory of a particular educational institution. Is shown that the critical position of this definition is the awareness of value-semantic landmarks, which become the basis on the way from the emergence of the pedagogical idea (innovation), choosing the direction of innovative search and building an innovative trajectory of development in a particular educational institution to create a model of innovative development of such institution as a whole. The author argues that the separation and development of value-semantic orientations of teachers and, above all, heads of educational institutions in the context of innovation is the basis for creating optimal conditions for research and experimental work in modern educational institutions.